Etika Komunikasi Islam Dalam Pemberitaan Genosida Gaza Pada Akun Instagram @Medan Talk - Saritza, Zahra; Sazali, Hasan (Wardah, 2024)
This study aims to examine Islamic communication ethics as manifested in news captions about the Gaza genocide posted on the Instagram account @Medan between October and December 2023. The significance of @Medan Talk as an influential source of information in Medan City led to its selection as the subject of study. This study employed the qualitative method, precisely the qualitative content analysis technique. The research findings revealed that the Islamic communication ethics contained in the captions include qaulan sadida, qaulan baligha, qaulan layyina, qaulan ma'rufa, qaulan maysura, and qaulan karima in reporting on the genocide in Gaza, with two Islamic communication ethics, qaulan baligha and qaulan maysura, dominating. This study's Islamic communication ethics adapt to general communication ethics, such as being polite, honest, not rude, not provocative, and accessible to ethnicity, religion, race, and group elements. Hopefully, this research can provide a basis for further research to investigate news on other platforms and with broader discussion topics.